Ghrelin Predicts Stimulant and Sedative Effects of Alcohol in Heavy Drinkers. (16th November 2022) - Ralevski, Elizabeth; Horvath, Tamas L; Shanabrough, Marya; Newcomb, Jenelle; Pisani, Emily; Petrakis, Ismene
Abstract: Aim: The aim of this study was to examine the relationship between ghrelin levels and the subjective effects of alcohol in heavy drinkers, and to compare them to healthy controls. Methods: Ghrelin levels were collected as part of two laboratory studies. Both groups received either IV infusion of saline or high dose of alcohol (100 mg%). In the study of heavy drinkers, ghrelin was gathered on all subjects, but data was analyzed only for participants who received placebo (N=12). Healthy controls (N=20) came from another study that collected data on family history. Ghrelin levels and measures of alcohol effects (BAES, VAS, NDS, YCS [see manuscript for details]) were collected at 4 timepoints: baseline, before infusion, during infusion and after infusion. Results: IV alcohol significantly reduced ghrelin levels and higher fasting ghrelin levels were associated with more intense subjective alcohol effects. There were no differences in fasting ghrelin levels or subjective effects between heavy drinkers and controls. However, while both groups showed similar decline in ghrelin levels following alcohol infusion, on the placebo day, ghrelin levels in the healthy subjects increased significantly and exponentially over time while for the heavy drinkers ghrelin levels remained flat. Conclusions: Our findings support the role of ghrelin in reward mechanisms for alcohol. Contrary to others, we found no differences in fasting ghrelin levels or subjective experiences of alcohol between heavy drinkers and healthy controls. However, the group differences on the IV placebo day may be a possible indication of ghrelin abnormalities in heavy drinkers.